Feather deformation of shuttlecock - Goh, Darren Ngak Tat (Nanyang Technological University, 2020)
Badminton is a very popular sport that is played casually and competitive. Major competitions around the world uses natural feather shuttlecocks due to its consistency and stability. However, the durability of these natural feather shuttlecocks seems to be an issue as the feathers start to deform after repetitive high impact hits. The aim of this Final Year Project is to test the durability of shuttlecocks and track its feathers’ deformation. To ensure fairness and unbiased testing and analysis, blind testing is conducted in this experiment, which means that no details of the shuttlecock will be made known to the tester. The three types of shuttlecocks put into testing are: 1) Type A Shuttlecock 2) Type B Shuttlecock 3) Type C Shuttlecock Five sets of the above-mentioned shuttlecocks will go through a durability test. The durability test conducted in this experiment is a modified durability test from the Badminton World Federation (BWF). It is performed by putting the test shuttlecocks through a series of 90 hits and recording the damages sustained after every interval of 10 hits. The damages sustained on the feather are also photographed to track the deformation of the feathers. Analysis of the results revealed that Type A shuttlecocks sustained the most damage, while Type B and Type C shuttlecocks sustained similar amounts of damage. The results indicate that Type A shuttlecocks are the least durable, while Type B and Type C shuttlecocks have similar durability. On this basis, it is recommended that further testing is done to find out the more durable shuttlecock type between Type B and Type C shuttlecocks.